2011
DOI: 10.22514/sv61.052011.1
|View full text |Cite
|
Sign up to set email alerts
|

The endocannabinoid system in sepsis – a potential target to improve microcirculation?

Abstract: During the last decade, research has identified the endocannabinoid system (ECS) as a key regulator of essential physiological functions, including the regulation of microvascular and immune function. Indeed, increasing evidence now suggests that release of endocannabinoids and activation of cannabinoid receptors occurs during sepsis and that manipulation of the ECS may represent an important therapeutic target to improve microcirculation in sepsis. In this review, the pharmacology and physiology of the ECS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Recently, several studies have reported that modulating CB 2 receptors in experimental models of sepsis decreased inflammation (Lehmann et al ., 2011; 2012), and deleting these receptors reduced survival (Tschop et al ., ). Attenuation of the inflammatory response by activation of CB 2 receptors has also been reported in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have reported that modulating CB 2 receptors in experimental models of sepsis decreased inflammation (Lehmann et al ., 2011; 2012), and deleting these receptors reduced survival (Tschop et al ., ). Attenuation of the inflammatory response by activation of CB 2 receptors has also been reported in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, CB2 are localized primarily in immune cells such as lymphocytes, macrophages and neutrophils and are responsible for immunomodulatory effects of cannabinoids. (1,3,4) While THC is a low-efficacy partial agonist of cannabinoid receptors, the synthetic cannabinoids are high-potency full agonists for CB1 receptors. (5) Most synthetic cannabinoids are not currently found using routine toxicology screening as they contain synthetic cannabinoids from different chemical classes.…”
Section: Introductionmentioning
confidence: 99%